Effects of Cutting Parameters on Drill Wear during Bone Drilling - Jean Gustave Tsiagadigui; Marie-Ange Ngo Yamben; Paul William Mejouyo Huisken; Marc Leroy Guifo; Loïc Fonkoue; Handy Eone; Jean Bahebeck; Ebenezer Njeugna; Maurice Aurélien Sosso (HEALTH SCIENCES AND DISEASE, 2023)
ABSTRACT Introduction. This study focuses on the analysis of the evolution of drill bit wear as a function of the cutting parameters and the number of holes in the case of bone drilling. Materials and methods. The holes are made with drill bits 3.2mm in diameter on the tibia bones of a bovine aged about one year. Rotational speeds of 100, 200 and 300 rpm as well as feed rates of 30 and 60 mm/min are adopted during drilling. Drill bits are used to make 2, 4, 6, 8 and 10 holes and the total hole thickness is assessed. The locks are then analyzed by digital microscopy and a new lock serves as a reference. Results. The quantitative evaluation of the wear shows that the width of the central edge increases significantly with the number of drill holes and the rotational speed. The feed rate has very little effect on this parameter. The vertex angle, although slightly influenced by the number of holes, remains almost insensitive to the variation of the cutting parameters. Qualitative analysis shows moderate wear after 4 to 6 piercings. This wear becomes severe after 10 holes, especially at high rotation speeds (300 rpm) with the appearance of large plastic deformations and circular streaks on the cutting edge. Conclusion. This study suggests not to exceed 4 reuses of the same bit in the case of non-lubricated drilling. RÉSUMÉ Introduction. Cette étude porte sur l'analyse de l'évolution de l'usure des mèches en fonction des paramètres de coupe et du nombre de trous durant le perçage osseux. Matériels et méthodes. Les trous sont réalisés avec des mèches de 3,2 mm de diamètre sur des tibias d'os bovin âgé d'un an. Des vitesses de rotation de 100, 200 et 300 tr/min ainsi que des vitesses d'avance de 30 et 60 mm/min sont adoptées pour la réalisation des essais. Les mèches sont utilisées pour réaliser 2, 4, 6, 8 et 10 trous et l'épaisseur totale du trou est évaluée. Les mèches sont ensuite analysées par microscopie numérique avec une mèche neuve servant de référence. Résultats. L'évaluation quantitative de l'usure montre que la largeur de l'arête centrale augmente considérablement avec le nombre de trous percés et la vitesse de rotation. La vitesse d'avance a très peu d'influence sur ce paramètre. L'angle au sommet, bien que légèrement influencé par le nombre de trous, reste presque insensible à la variation des paramètres de coupe. L'analyse qualitative montre une usure modérée à partir de 4 à 6 perçages. Cette usure devient sévère après 10 trous, surtout à des vitesses de rotation élevées (300 tr/min) avec l'apparition de grandes déformations plastiques et de stries circulaires sur l'arête de coupe. Conclusion. Cette étude suggère de ne pas dépasser 4 réutilisations de la même mèche dans le cas d'un perçage non irrigué.